Relationship between democracy and development: Evidence from Bangladesh - Zakaria, Sultan Mohammed (BRAC Institute of Governance and Development (BIGD), 2022)
The paper examines the effect of democracy on the development outcomes of Bangladesh for the period 1972 to 2016. It analyzes both the long-run relation and the direction of causality using the Vector Error Correction Model (VECM) framework. The paper uses the Polity data constructed by the Polity IV project as the proxy for democracy, and GDP per capita (constant 2010 US$) as the proxy for development. The estimation based on VEC Model suggests the coefficients of co-integration equations do not adjust towards either long-run or short-run equilibrium, meaning that the results find no evidence of any relationship between democracy and economic development in Bangladesh.